2014
DOI: 10.7314/apjcp.2014.15.14.5895
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms in Stress-Related TNFα and NPY Genes with the Metabolic Syndrome in Han and Hui Ethnic Groups

Abstract: Background: Metabolic syndrome (MS) is a cluster of complicated disorders caused by the interactive influencing factors of heredity and environment, which predisposes to many cnacers. Results from epidemic research indicate that stress is tightly related to the pathogenesis of MS and neoplasia. This paper aims to investigate the association between psychological stress and MS with respect to the tumor necrosis factor alpha (TNFα) and neuropeptide Y (NPY) genes in the Han and Hui ethnic groups. Methods: All sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…A total of 104 adolescents with overweight and obesity (46 girls, 58 boys) were included in the study. The mean age was 16.01 ± 2.91 (16)(17)(18) years, mean weight of 52.98± 2.2 kg, and mean BMI 23.31±6.83 kg/m 2 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 104 adolescents with overweight and obesity (46 girls, 58 boys) were included in the study. The mean age was 16.01 ± 2.91 (16)(17)(18) years, mean weight of 52.98± 2.2 kg, and mean BMI 23.31±6.83 kg/m 2 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Different studies have evaluated the TNF-α gene -308G/A polymorphism relationship to IR and lipid abnormalities in obese children suggesting that the -308G/A variation in this gene does not seem to play an important role in the setting down of obesity and IR. 17,18 However, an Australian study, in obese non-diabetic subjects, investigated whether a common polymorphism in the promoter region ((-308 G/A) of the TNF-α gene was associated with increased risk for the development of IR. The study showed that the polymorphism was associated with increased IR in obese subjects, possibly as a result of increased TNF-α production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chinese Hui ethnic group descended from Arab and Persian Muslim immigrants who came to China and married local girls hundreds or even thousands of years ago [ 28 ]. However, Hui people adhere to Islamic principles [ 29 ]. To retain religious purity and group identity, most Hui people have always isolated themselves socially from other people in enclaves.…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) have emerged as genetic markers of choice because of their high density and relatively even distribution across the human genome, and SNPs have been used for fine mapping of disease loci and for candidate gene association studies [ 9 ]. Several investigations have recently shown that differences existed in psychological stress susceptibility, cancer susceptibility and cancer prognosis between Chinese Hui and Chinese Han [ 10 , 11 , 12 ]. However, there are still a lot of works needed to be done to ultimately unveil the genetic differences between these two groups of people.…”
Section: Introductionmentioning
confidence: 99%